Comparison Of The Anthologies "Tazkirai Shuaro" And ’fMajmua Si Pairavi Feruzshohiy’t - do’stova, surayyo (FILOLOGIYA UFQLARI JURNALI, 2022)
This article provides information about Hasanmurad Laffasi’s anthology "Tazkirai Shuaro" and compares it with Ahmadjon Tabibirs anthology "Maimua si shuaroi payravi Feruzshohiy". The similarities and differences between the works of TazkiraiShuaro and the poems of these anthologies written by poets are studied comparatively and made conclusions.